On Negative Slope of Probe Characteristics in Magnetized Plasmas. Issue 3 (April 2014) - Mihaila, I.; Costea, S.; Costin, C.; Popa, G.
Abstract In the present contribution, experimental and numerical simulation results are presented on the influence of the electrons reflected by the insulator shaft of the probe on both probe characteristic and local disturbance produced by these electrons within relatively strong magnetized plasmas. The reduction mechanism of the electron component of the probe characteristic with increasing the magnetic field strength can also be investigated by the new experimental setup. Both electron current intensity increase and diminish of the negative slope region of the current‐voltage characteristics are explained based on the electrons kinetics near the probe. Essentially, the explanation is based on the idea that slow electrons with kinetic energy lower than eVf, where Vf is the floating potential of any surface in contact with the local plasma, are reflected. Consequently, magnetized electrons moving along the magnetic field lines close and parallel to the probe surface, but still not collected by the positive bias of the probe, are reflected by the floating potential of the dielectric shaft surface. Consequently, both reflection and possible collision process increase the probability for electrons collection by the probe leading to an increase of the electron saturation current intensity followed by negative slope as negative resistance predicted by adiabatic‐limit approximation proposed by Laframboise and Rubinstein. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)